Gambaran Kebiasaan Merokok dengan Kejadian Penyakit Paru Obstruksi Kronik (Ppok) Dibalai Besar Kesehatan Paru Masyarakat Makassar - Nufus, Hayatun (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2024)
Chronic obstructive pulmonary disease (COPD) is a disease characterized by airflow obstruction in the airways that is not completely reversible. The airflow obstruction that occurs is progressive, related to the lung's inflammatory response to toxic or dangerous particles or gases. Emphysema and chronic bronchitis are often caused by smoking and are included in the COPD group. Based on data from the Makassar Community Lung Health Center, The number of COPD sufferers has decreased over the last three years. In 2019 there were 521 COPD patients. The aim of this study was to determine the description of smoking habits and the incidence of COPD. This research used descriptive research with 38 samples from 129 populations diagnosed with COPD at the Makassar Community Lung Health Center. where the description of smoking habits and the incidence of COPD for each subject/research sample was observed only once. The results of this study showed that of the 38 COPD respondents, 20 people (52.6%) had heavy smoking habits, and 18 people (47.4%) had moderate smoking habits. The conclusion of the research is an overview of smoking habits and the incidence of COPD at the Community Lung Health Center. It is recommended that everyone immediately stop smoking to avoid COPD and health workers are expected to increase education about the dangers of smoking